Addition of Logarithms

The definition of a logarithm is:


logax=blog_a⁡x=b
X=abX=a^b

Where:
aa is the base of the exponent
XX is what appears inside the log, can also appear in parentheses
bb is the exponent we raise the log base to in order to get the number that appears inside the log.

Adding logarithms with the same base is based on the following rule:


logax+logay=loga(xy)log_a⁡x+log_a⁡y=log_a⁡(x\cdot y)

Adding logarithms with different bases is done by changing the base of the log using the following rule:

logaX=logbase we want to change toXlogbase we want to change toalog_aX=\frac{log_{base~we~want~to~change~to}X}{log_{base~we~want~to~change~to}a}

Practice The Sum of Logarithms

Examples with solutions for The Sum of Logarithms

Exercise #1

2log82+log83= 2\log_82+\log_83=

Video Solution

Step-by-Step Solution

2log82=log822=log84 2\log_82=\log_82^2=\log_84

2log82+log83=log84+log83= 2\log_82+\log_83=\log_84+\log_83=

log843=log812 \log_84\cdot3=\log_812

Answer

log812 \log_812

Exercise #2

12log24×log38+log39×log37= \frac{1}{2}\log_24\times\log_38+\log_39\times\log_37=

Video Solution

Step-by-Step Solution

We break it down into parts

log24=x \log_24=x

2x=4 2^x=4

x=2 x=2

log39=x \log_39=x

3x=9 3^x=9

x=2 x=2

We substitute into the equation

122log38+2log37= \frac{1}{2}\cdot2\log_38+2\log_37=

1log38+2log37= 1\cdot\log_38+2\log_37=

log38+log372= \log_38+\log_37^2=

log38+log349= \log_38+\log_349=

log3(849)=log3392 \log_3\left(8\cdot49\right)=\log_3392 x=2 x=2

Answer

log3392 \log_3392

Exercise #3

3log49+8log413= 3\log_49+8\log_4\frac{1}{3}=

Video Solution

Step-by-Step Solution

Where:

3log49=log493=log4729 3\log_49=\log_49^3=\log_4729

y

8log413=log4(13)8= 8\log_4\frac{1}{3}=\log_4\left(\frac{1}{3}\right)^8=

log4138=log416561 \log_4\frac{1}{3^8}=\log_4\frac{1}{6561}

Therefore

3log49+8log413= 3\log_49+8\log_4\frac{1}{3}=

log4729+log416561 \log_4729+\log_4\frac{1}{6561}

logax+logay=logaxy \log_ax+\log_ay=\log_axy

(72916561)=log419 \left(729\cdot\frac{1}{6561}\right)=\log_4\frac{1}{9}

log491=log49 \log_49^{-1}=-\log_49

Answer

log49 -\log_49

Exercise #4

log7x+log(x+1)log7=log2xlogx \log7x+\log(x+1)-\log7=\log2x-\log x

?=x ?=x

Video Solution

Step-by-Step Solution

Defined domain

x>0

x+1>0

x>-1

log7x+log(x+1)log7=log2xlogx \log7x+\log\left(x+1\right)-\log7=\log2x-\log x

log7x(x+1)7=log2xx \log\frac{7x\cdot\left(x+1\right)}{7}=\log\frac{2x}{x}

We reduce by: 7 7 and by X X

x(x+1)=2 x\left(x+1\right)=2

x2+x2=0 x^2+x-2=0

(x+2)(x1)=0 \left(x+2\right)\left(x-1\right)=0

x+2=0 x+2=0

x=2 x=-2

Undefined domain x>0

x1=0 x-1=0

x=1 x=1

Defined domain

Answer

1 1

Exercise #5

log103+log104= \log_{10}3+\log_{10}4=

Video Solution

Answer

log1012 \log_{10}12

Exercise #6

log974+log912= \log_974+\log_9\frac{1}{2}=

Video Solution

Answer

log937 \log_937

Exercise #7

log24+log25= \log_24+\log_25=

Video Solution

Answer

log220 \log_220

Exercise #8

log2x+log2x2=5 \log_2x+\log_2\frac{x}{2}=5

?=x

Video Solution

Answer

8 8

Exercise #9

Find X

log84x+log8(x+2)log83=3 \frac{\log_84x+\log_8(x+2)}{\log_83}=3

Video Solution

Answer

1+312 -1+\frac{\sqrt{31}}{2}

Exercise #10

log3x+log(x1)=3 \log3x+\log(x-1)=3

?=x ?=x

Video Solution

Answer

18.8 18.8

Exercise #11

log4x+log4(x+2)=2 \log_4x+\log_4(x+2)=2

Video Solution

Answer

1+17 -1+\sqrt{17}

Exercise #12

?=a

ln(a+5)+ln(a+7)=0 \ln(a+5)+\ln(a+7)=0

Video Solution

Answer

6+2 -6+\sqrt{2}

Exercise #13

log45+log423log42= \frac{\log_45+\log_42}{3\log_42}=

Video Solution

Answer

log810 \log_810

Exercise #14

log4x+log2log9=log24 \log4x+\log2-\log9=\log_24

?=x

Video Solution

Answer

112.5 112.5

Exercise #15

log9e3×(log224log28)(ln8+ln2) \log_9e^3\times(\log_224-\log_28)(\ln8+\ln2)

Video Solution

Answer

6 6